Development and Validation of a Brief Form of the Childhood Adversities Questionnaire Among a Population of Mood Disorders. Issue 3 (February 2022) - Li, Muzi; Cassis, Tamara; D'Arcy, Carl; Low, Nancy; Meng, Xiangfei
Childhood adversities have significantly negative consequences on physical and mental health. The Childhood Experience of Care and Abuse Questionnaire, Version 3 (CECA.Q3) interview, as an extended version of the CECA.Q, is widely used in the assessment of childhood adversities. Although its reliability and validity have been demonstrated, the application of CECA.Q3 is limited due to its intensive and lengthy interview. This article aimed to develop and validate a brief form of the CECA.Q3 (CECA.Q3-BF) among a population of mood disorders. Data analyzed were from a clinical sample of 210 patients with mood disorders. Data were randomly split into training and testing datasets. The training data set was used for scale reduction by applying principal component factor analysis, while the testing one was used for cross-validation to examine whether the CECA.Q3-BF could have a good yield of accuracy. The optimal cutoff points of the CECA.Q3 were also tested. Overall, four out of eight subscales had items reduction without compromising their accuracy of measurements for childhood adversities. They are Antipathy (reduced by four items), Neglect (reduced by five items), Psychological Abuse (reduced by 15 items), and Role Reversal (reduced by 11 items). The CECA.Q3-BF removed 35 items (35/100, 35%) from the full CECA.Q3. The accuracy of CECA.Q3-BF was validated in the testing dataset. The CECA.Q3-BF offers a brief but good accuracy of measure for childhood adversities. Future studies are warranted to further validate this brief form. The CECA.Q3-BF is expected to improve the application of CECA.Q3 in clinical and epidemiological surveys, as it significantly reduces the length of the interview and therefore has better compliance.